Polyphenols as fungal phytotoxins, seed germination stimulants and phytoalexins - Cimmino, Alessio; Andolfi, Anna; Abouzeid, Mohamed; Evidente, Antonio (PHYTOCHEMISTRY REVIEWS, 2013)
This review deals with the sources and chemical and biological characterization of phytotoxic polyphenols produced essentially by pathogenic fungi of forest and crop plants and of weeds. Their potential use as natural herbicides and fungicides is discussed. The use of some polyphenols which could be applied as an alternative method to control parasitic weeds, the so called ``suicidal germination{''}, will be covered. The sources and the isolation and identification of polyphenols produced by some crop plants in consequence of the attack of pathogenic fungi as plant defence compounds (phytoalexins), are also described.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Phytoalexins; Phytotoxins; polyphenols; Seed germination stimulants